2014
DOI: 10.1007/s10549-014-3169-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tamoxifen and oestrogen on histology and radiographic density in high and low mammographic density human breast tissues maintained in murine tissue engineering chambers

Abstract: Mammographic density (MD) is a strong risk factor for breast cancer. It is altered by exogenous endocrine treatments, including hormone replacement therapy and Tamoxifen. Such agents also modify breast cancer (BC) risk. However, the biomolecular basis of how systemic endocrine therapy modifies MD and MD-associated BC risk is poorly understood. This study aims to determine whether our xenograft biochamber model can be used to study the effectiveness of therapies aimed at modulating MD, by examine the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…Therefore, it is worthwhile reviewing the established and possible mechanisms through which tamoxifen could impact both MD and BC. In terms of tamoxifen effects on breast tissue, the drug was noted to cause a reduction in the stromal component of biochamber-implanted HMD tissue, which was associated with reduction of MD [66]. In addition to contributing to an HMD status [67], a high stromal density contributes to a higher BC risk in animals [68, 69].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is worthwhile reviewing the established and possible mechanisms through which tamoxifen could impact both MD and BC. In terms of tamoxifen effects on breast tissue, the drug was noted to cause a reduction in the stromal component of biochamber-implanted HMD tissue, which was associated with reduction of MD [66]. In addition to contributing to an HMD status [67], a high stromal density contributes to a higher BC risk in animals [68, 69].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is likely that oestradiol and progesterone synergistically cause a transient rise in MD in the luteal phase [ 4 ]. We showed that MD of human breast tissue in our xenograft murine engineering chambers was influenced by the murine peripartum states as well as by tamoxifen treatment of the nonobese diabetic/severe combined immunodeficiency NOD SCID mice [ 75 , 76 ]. Our unique within-individual paired analyses eliminated confounders such as different stages of the menstrual cycle or menopausal status among women; however, we did not observe any significant difference in the percentage expression of ER and PR between HMD and LMD tissue within the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have found increased stromal expression of ER and epithelial or stromal expression of PR in dense tissue samples from women at population risk or increased risk (80,81). Laboratory studies using mouse models and human tissue xenografts have shown that tamoxifen treatment promotes remodelling of stroma to a tumour-inhibitory phenotype, with reduced extracellular matrix turnover and decreased stromal tissue (82,83).…”
Section: Increased Breast Cancer Riskmentioning
confidence: 99%